Metabarcoding Cyanobacteria in coastal waters and sediment in central and southern Adriatic Sea - Kolda, Anamarija (Array, 2020)
Seasonal sampling of the seawater column and sediment in Adriatic coastal areas affected by various anthropogenic activities, primarily aquaculture, was conducted during 2017. In total, 32 samples from two sites (central and southern Adriatic) were analysed by 16S rRNA amplicon sequencing. This approach was selected to test the possibilities of using metabarcoding in studying marine cyanobacteria, exploring their ecology and potential as an indicator group in anthropologically stressed coastal environments. Additionally, physicochemical water column parameters, sediment granulometry and composition were assessed. Water column revealed a seasonal variation of amplicon sequencing variants (ASVs) closely related to Cyanobium PCC-6307, Prochlorococcus MIT9313 and Synechococcus CC9902, as well as seasonal grouping of physico-chemical parameters in PCA analysis. Sediment analysis uncovered greater community richness of 13 cyanobacterial genera and two uncultured groups. The most abundant in sandy gravels and gravelly sand type of sediments were ASVs closely related to Pleurocapsa PCC-7319 and Xenococcus PCC-7305. Furthermore, identified cyanobacterial ASVs predominantly displayed similarity to isolates from tropical areas (e.g. Neolyngbya, Chroococcidiopsis, Trichodesmium, etc.), which could indicate the tropicalization process already ongoing in the fish fauna of the Adriatic Sea.